Multi-input Transformer Coupled(tied) Bidirectional DC-DC Converter For Renewable Energy Applications - Sunil Kumar, M.; Hari Priya, T. (International Journal of Engineering and Technology, 2018)
This paper gives an explanation on merging of multi renewable sources with an efficient control topology using multi-input converter of transformer tied bidirectional dc-dc converter. This multi-source converter has a desire which can fulfill the load demand, and can handle the sources even in intermittent of the nature. A bidirectional buck/boost converter is used to utilize the PV source accompanied with battery charging/discharging control; while a transformer tied current-fed boost half bridge converter is used to harness the power from fuel cell. If needed single-phase full-bridge inverter is used to feed the AC loads. This converter has less switching components, which results in lessen amount of power converting stages, make better the reliability and boost up efficiency of the system. Simulation results are carried out by using MATLAB/Simulink show the efficacy of multi input converter under various modes of operation.Â  Â